\(\left(6400+4600\right)-7y=3839\)
\(11000-7y=3839\)
\(7y=11000-3839\)
\(7y=7161\)
\(y=7161:7\)
\(y=1023\)
Vậy \(y=1023\)
Tham khảo nhé~
( 6400 + 4600 ) - 7y = 3839
=> 110000 - 7y = 3839
=> 7y = 110000 - 3839
=> 7y = 7161
=> y = 7161 : 7
=> y = 1023
Vậy y = 1023
Học tốt #
(6400+4600)-7y=3839
7y = (6400+4600)-3839
7y = 11000 -3839
7y = 7161
y = 7161:7
y = 1023
học tốt nhoa!!!
\(\left(6400+4600\right)-7y=3839\)
\(11000-7y=3839\)
\(7y=11000-3839\)
\(7y=7161\)
\(y=7161:7\)
\(y=1023\)
\(\text{Tìm }y\text{ : }\)
\(\left(6400+4600\right)-7y=3839\)
\(110000-7y=3839\)
\(7y=110000-3839\)
\(7y=7161\)
\(y=7161\text{ : }7\)
\(y=1023\)
(6400+4600)−7y=3839
\(\Rightarrow\)11000−7y=3839
\(\Rightarrow\)7y=11000−3839
\(\Rightarrow\)7y=7161
\(\Rightarrow\)y=7161:7
\(\Rightarrow\)y=1023
Vậy y=1023
( 6400 + 4600 ) - 7y = 3839
<=> 11000 - 7y = 3839
<=> 7y = 7161
<=> y = 7176 : 7
<=> y = 1023